THE ROLE OF ELECTORAL CAMPAIGNS IN STRENGTHENING DEMOCRATIC PARTICIPATION (A Case Study of The 2024 Legislative Election In North Sumatra) - Ahmad Sampurna Rambe; Elman; Latifah Rahmawati; Defi Nurfajaria; Raysa Finarik Rambe; Fauzi Iqbal (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to examine how electoral campaigns contribute to strengthening democratic participation in the 2024 Legislative Election in North Sumatra. Conceptually, electoral campaigns serve as a vital instrument in democratic systems, functioning as a communication bridge between candidates and voters that can enhance political awareness and encourage civic engagement in the electoral process. The research explores the dynamics of campaign implementation in North Sumatra, including the strategies employed by political parties and legislative candidates, the influence of social media, and the role of civil society. The findings indicate that informative and inclusive campaigns have a significantly positive impact on voter participation, particularly among young voters and first-time voters. However, several challenges remain, such as vote-buying practices, the spread of misinformation, and low political literacy, all of which can hinder democratic consolidation at the local level. This study highlights the importance of implementing stricter campaign regulations, continuous political education, and collaboration among the General Elections Commission (KPU), political parties, and civil society organizations to foster a more participatory and democratic electoral process. A qualitative case study approach was adopted to examine the function of electoral campaigns in enhancing democratic participation during the 2024 Legislative Election in North Sumatra. The qualitative method was chosen for its ability to investigate socio-political phenomena in a contextual and in-depth manner, based on the experiences and perspectives of individuals directly involved in the campaigns. Campaigns that emphasized information-sharing, inclusivity, and the use of social media were found to be effective in stimulating participation, especially among youth and novice voters. Nevertheless, persistent challenges such as money politics, the spread of hoaxes, and weak political literacy continue to hinder the improvement of democratic quality at the local level. Therefore, campaign regulations particularly those concerning digital media must be reinforced, and public political awareness must be improved so that voters can think critically and are not easily influenced by disinformation or transactional politics.